Heterogeneous Family of Cyclomodulins: Smart Weapons That Allow Bacteria to Hijack the Eukaryotic Cell Cycle and Promote Infections - El-Aouar Filho, Rachid A.; Nicolas, Aurélie; De Paula Castro, Thiago L.; Deplanche, Martine; De Carvalho Azevedo, Vasco A.; Goossens, Pierre L.; Taieb, Frédéric; Lina, Gerard; Le Loir, Yves; Berkova, Nadia (Frontiers in Cellular and Infection Microbiology, 2017)
Some bacterial pathogens modulate signaling pathways of eukaryotic cells in order to subvert the host response for their own benefit, leading to successful colonization and invasion. Pathogenic bacteria produce multiple compounds that generate favorable conditions to their survival and growth during infection in eukaryotic hosts. Many bacterial toxins can alter the cell cycle progression of host cells, impairing essential cellular functions and impeding host cell division. This review summarizes current knowledge regarding cyclomodulins, a heterogeneous family of bacterial effectors that induce eukaryotic cell cycle alterations. We discuss the mechanisms of actions of cyclomodulins according to their biochemical properties, providing examples of various cyclomodulins such as cycle inhibiting factor, γ-glutamyltranspeptidase, cytolethal distending toxins, shiga toxin, subtilase toxin, anthrax toxin, cholera toxin, adenylate cyclase toxins, vacuolating cytotoxin, cytotoxic necrotizing factor, Panton-Valentine leukocidin, phenol soluble modulins, and mycolactone. Special attention is paid to the benefit provided by cyclomodulins to bacteria during colonization of the host.